Preparation of nano-crystalline boehmite as a gamma-alumina source for the production of Na.beta-Al203 solid electrolyte - Pimsorn P. (2014)
Nano-crystalline boehmite (AIOOH) proposed as a precursor for γAl2O3 production was prepared using precipitation process. The mixture of two starting solutions of AIN3O 9.9H2O and Na2Al2O4 was formed and NaOH was used as pH adjustment. Various preparation conditions, starting pH and temperatures were applied. The results suggested that high purity AlOOH powder could be obtained at solution temperature above 60°C and starting pH was in range 7-11. Their crystalline size increased from 2.4 to 3.9 nm with increasing pH. According to the results, AlOOH from pH 8 and temperature 80°C was selected for producing the γ-AI2O 3 by calcination in the temperature range of 350°C-1100°C. Transformation from AlO(OH) toγ-Al2O3 could be readily observed from the whole temperature range and γ-Al 2O3 crystalline size was increased with increasing calcination temperature. After the temperature reached 1100°C, transformation to α- and θ- phases were also found. Morphology of γ-AI2O3 powder shows a strong aggomeration. © 2008 Trans Tech Publications, Switzerland.